2018
DOI: 10.1080/2162402x.2018.1524694
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic vaccination using minimal HPV16 epitopes in a novel MHC-humanized murine HPV tumor model

Abstract: Therapeutic vaccination as a treatment option for HPV-induced cancers is actively pursued because the two HPV proteins E6 and E7 represent ideal targets for immunotherapy, as they are non-self and expressed in all tumor stages. MHC-humanized mice are valuable tools for the study of therapeutic cancer vaccinesgiven the availability of a suitable tumor model. Here, we present for the first time an HPV16 tumor model suitable for fully MHC-humanized A2.DR1 mice, PAP-A2 cells, which in contrast to existing HPV16 tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Moreover, these mouse models limit the choice of immune epitopes, and therefore might not be used to test those epitopes found exclusively in human patients. Recently, MHC-humanized mouse HPV tumor models have been developed (218), which could potentially be used as new vaccine testing platforms in the future. Nevertheless, the limitation of these humanized mouse models still exists as they are not able to mimic the entire human immune system.…”
Section: Immune Evasion Of Hpv By Modulating the Immune Networkmentioning
confidence: 99%
“…Moreover, these mouse models limit the choice of immune epitopes, and therefore might not be used to test those epitopes found exclusively in human patients. Recently, MHC-humanized mouse HPV tumor models have been developed (218), which could potentially be used as new vaccine testing platforms in the future. Nevertheless, the limitation of these humanized mouse models still exists as they are not able to mimic the entire human immune system.…”
Section: Immune Evasion Of Hpv By Modulating the Immune Networkmentioning
confidence: 99%
“…We previously identified immunogenic epitopes among our data set of HLA-A2 binding peptides through IFNg responses of peripheral blood mononucleated cells from healthy donors (62). Four selected epitopes were validated in vivo in an MHC-humanized mouse model (64). This demonstrates that MHC class-I binding prediction, applying the commonly used strong and intermediate binding affinity thresholds, provides high prediction specificity.…”
Section: Discussionmentioning
confidence: 85%
“…[6] To address the safety issues and regulatory challenges associated with live vectors, peptide-based subunit vaccines with HPV16 E6/E7 antigens have been studied extensively. [7,41,42] However, peptide-based subunit vaccines generally suffer from limited anti-tumor efficacy due to inefficient antigen delivery to lymphoid tissues and the lack of appropriate innate immune stimulation. [4,12] In our previous work, we have shown that the nanodisc vaccine technology administered s.c. can efficiently drain to LNs and generate potent antigenspecific T cell responses.…”
Section: Resultsmentioning
confidence: 99%